2021
DOI: 10.20944/preprints202105.0212.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Another Look at the Water Phases that Exist Under Room Conditions

Abstract: A brief review of the history of the problem is intended to trace the progress in the development of scientific views on the structure of water. The discoveries in this area made in the first half of the last century are considered in comparison with modern data. It is shown that due to the de facto ban on the study of the structure of water in 1971, work in this direction was frozen for a long time. The paradox is that many forgotten truths have been independently "rediscovered" in our time, which speaks of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…The physicochemical properties of irrigation water can be manipulated by several energy-based treatments [13]. Decades of research have shown that bulk water exposed to energy sources that strengthen or shorten the hydrogen bonds in water molecules such as infrared radiation, magnetic fields, sonic waves, mechanical vibrations, or low temperatures will add structure to water [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical properties of irrigation water can be manipulated by several energy-based treatments [13]. Decades of research have shown that bulk water exposed to energy sources that strengthen or shorten the hydrogen bonds in water molecules such as infrared radiation, magnetic fields, sonic waves, mechanical vibrations, or low temperatures will add structure to water [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Structured water is a semi-crystalline form of water with a higher viscosity, lower density, and surface tension [21,28,31]. The physicochemical properties of structured water include increased electrical conductivity and pH [13,31]. Water conductivity and pH increase with an increasing ratio of structured water to unstructured water due to an increase in delocalized, and quasi-free electrons and protons that form vortices in and around the hexagonal rings of water [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%